The role of integrin-linked kinase in the molecular architecture of focal adhesions - Elad, Nadav; Volberg, Tova; Patla, Israel; Hirschfeld-Warneken, Vera C.; Grashoff, Carsten; Spatz, Joachim P.; Fässler, Reinhard; Geiger, Benjamin; Medalia, Ohad (Journal of cell science, 2013)
Skip to Next Section - Integrin-mediated focal adhesions (FAs) are large, multi-protein complexes that link the actin cytoskeleton to the extracellular matrix and take part in adhesion-mediated signaling. These adhesions are highly complex and diverse at the molecular level; thus, assigning particular structural or signaling functions to specific components is highly challenging. Here, we combined functional, structural and biophysical approaches to assess the role of a major FA component, namely, integrin-linked kinase (ILK), in adhesion formation. We show here that ILK plays a key role in the formation of focal complexes, early forms of integrin adhesions, and confirm its involvement in the assembly of fibronectin-bound fibrillar adhesions. Examination of ILK-null fibroblasts by cryo-electron tomography pointed to major structural changes in their FAs, manifested as disarray of the associated actin filaments and an increase in the packing density of FA-related particles. Interestingly, adhesion of the mutant cells to the substrate required a higher ligand density than in control cells. These data indicate that ILK has a key role in integrin adhesion assembly and sub-structure, and in the regulation of the FA-associated cytoskeleton.
Gesehen am 01.02.2021